ترجيحات الإمام الرازي في تفسيره "مفاتيح الغيب" آيات مختارة من سورة النساء = The concept of preferences in The view of Fakhr Al-Dīn Al-Rāzī in his tafsīr: Mafātiḥ Al-Ghaib - Elatrash, Radwan Jamal Yousef; M. Saleh, Otman Albadwi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يركز هذا البحث على إظهار منهج الإمام فخر الدين الرازي في ترجيحاته من خلال كتابه التفسير الكبير في سورة النساء، والناظر في تفسير فخر الدين الرازي يجد التباساً شديداً في تحديد القول المختار، والمعنى الراجح لتفسير آية ما، مما يشكل تحديًا كبيراً أمام الباحثين في هذا المجال، وجاء هذا البحث ليساهم في حل هذه المشكلة وإزالة هذا اللبس من خلال تبيين الأدلة إما بالجمع بينها أو الترجيح بمرجحات تم استنباطها أو استقراؤها من النصوص الشرعية أو اللغوية أو العقلية، والبحث بهذه الطبيعة يناسبه استخدام المنهج الاستقرائي والمنهج التحليلي، ومن أهم النتائج المتوقعة: إثبات أن التفسير الكبير ثري بعلم الترجيحات النقلية واللغوية والعقلية وخصوصاً في موضوعات سورة النساء. ********************************************************** This research aims at elucidating the methodology used by Imām Fakhr Al-Dīn Al-Rāzī in interpreting the holy Qur’ān through his unique interpretive work called Mafātiḥ Al-Ghaib (Keys to the Unseen) and later nicknamed Tafsīr Al-Kabīr (The Great Commentary). To fully assimilate the explanation of Imām Al-Rāzī was considered as a challenge among researchers which have been confused in determining the right accurate meanings of Qur’ān verses. Thus, this research arises to contribute to solve this problem via revealing the proofs either by combining the evidence or proposing the preferences that has been inferred or deduced from the legal, linguistic or mental texts. The research adopted the Inductive and analytical methods which are the most suitable methodology for this kind of researches. The researcher concluded that Tafsīr Al-Kabīr (The Great Commentary) is a rich book that contributed greatly to the dissemination of a rational approach to the Qur’ān exegesis by teaching the textual, linguistic and mental preferences, especially concerning the issues of Annisā’ (The women) Verse.